THE DEPLORABLE STATE OF THE BULGARIAN ECONOMY REQUIRES URGENT MEASURES FOR ITS MODERNIZATION, BUT CREATES ENORMOUS DIFFICULTIES FOR THE INVESTMENT PROCESS: THE DEPLORABLE STATE OF THE BULGARIAN ECONOMY REQUIRES URGENT MEASURES FOR ITS MODERNIZATION, BUT CREATES ENORMOUS DIFFICULTIES FOR THE INVESTMENT PROCESS - Totev, Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Our country and our small open economy is heavily dependent on the world market, as we have no practical impact on the development and functioning of this market, we consume all its positives and assets.